2004
DOI: 10.1111/j.1523-1739.2004.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Effects of Collecting Rattan Cane and Their Implications for Sustainable Harvesting

Abstract: Rattan, Old World climbing palm, is an extremely valuable nontimber forest product whose canes are gathered for both market and nonmarket uses. I evaluated the effects of harvesting commercial rattan, Calamus zollingeri Becc., on genet survival and ramet demography in two primary forest sites near Lore Lindu National Park in Sulawesi, Indonesia. I monitored 168 permanently marked C. zollingeri genets for 4 years and surveyed random transects for C. zollingeri genet and ramet populations and evidence of cane ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 24 publications
0
43
1
3
Order By: Relevance
“…The first narrative concerns the over-exploitation of rattan (Calamus spp. ), an internationally traded non-timber forest resource found in Central Sulawesi, Indonesia [31]. The second problem describes near-shore dynamite fishing in the Sunda Sea, Indonesia [32].…”
Section: Situational and Conceptual Knowledgementioning
confidence: 99%
“…The first narrative concerns the over-exploitation of rattan (Calamus spp. ), an internationally traded non-timber forest resource found in Central Sulawesi, Indonesia [31]. The second problem describes near-shore dynamite fishing in the Sunda Sea, Indonesia [32].…”
Section: Situational and Conceptual Knowledgementioning
confidence: 99%
“…Fieldwork revealed that the first two explanations are more plausible, especially because some dead individuals were found due to clear-cutting. Many plants are capable of supporting high levels of extraction due to their biological characteristics, such as life history and reproduction rate (Siebert 2004;Ticktin 2004). Characteristics inherent to angico are: initiation of the reproductive phase as early as the third year (Maia 2004), production of large amounts of fruit and seed, high rates of germination and survival and low mortality (Silva and Barbosa 2000).…”
Section: Population Structure and Extraction Of A Colubrinamentioning
confidence: 99%
“…In Malaysia, Sumatra and the Philippines, most important commercial rattan species are already threatened (Sunderland and Dransfield 2002). While collecting rattan is illegal in LLNP, approximately 18% of the park was estimated subject to intensive commercial cane harvesting, particularly of Calamus zollingeri, in the late 1990s and early 2000s (Siebert 2004). In addition, virtually all of the land surrounding LLNP is influenced by human activities such as conversion of forests into agroforestry systems or plantations and harvesting of forest products (Schulze et al 2004;Waltert et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological studies of rattan palms are so far limited to Thailand and West Malaysia (Bøgh 1996;Watanabe and Suzuki 2008), or have dealt with the commercially important rattan species Calamus zollingeri (Siebert 1993(Siebert , 2000(Siebert , 2004 and the sustainability of rattan harvesting in Sulawesi (Clayton et al 2002). Siebert (2005), working in southern LLNP between 830 and 1330 m elevation, found that while the density of rattan did not vary significantly with elevation, species richness of rattan was greatest between 1180 and 1280 m.…”
Section: Introductionmentioning
confidence: 99%